How Board Member’s Education Diversities and Financial Expertise Matter to Sustainability Report Disclosure: An Insight from Upper-echelon Theory - Fitriasari, Rizka; Soewarno, Noorlailie (Jurnal Aplikasi Manajemen, 2024)
Companies are recently developing corporate governance practices in order to manage and monitor sustainability issues, especially the role of the board of directors in the context of sustainability reports. The board of directors must be geared with sufficient expertise so that they can run their roles and functions effectively. This study aims to discover the potential influence of board members’ education diversities and financial expertise on sustainability report disclosure from the perspectives of upper-echelon theory. This study examines 1276 board members of 220 manufacturing companies listed on the Indonesia Stock Exchange. The data was obtained from the firms’ sustainability reports and was analyzed using content analysis and multiple regression analysis. A checklist containing 91 CSR disclosure items based on the Global Reporting Initiative was utilized. Content analysis was used to extract the CSR disclosure items from the sustainability reports. Based on the regression analysis, only the board members’ financial expertise matters to the extent of disclosure of sustainability reports, while education diversities are not influential. This study is important because it uses upper echelons theory to ascertain the influence of specific board attributes, namely board members’ education diversities and financial expertise, on sustainability report disclosure. As a result, it provides important implications for corporate governance regulators and different stakeholders from the perspective of sustainability report disclosure.